STRATEGI PEMERINTAH DESA MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PERENCANAAN PEMBANGUNAN DESA BERDASARKAN UNDANG-UNDANG NO. 3 TAHUN 2024 TENTANG DESA (STUDI KASUS DI DESA TANJUNG BERINGIN I, KECAMATAN SUMBUL, KABUPATEN DAIRI) - Br. Sihaloho, Juli Tiarma; Panjaitan, Maringan; Pasaribu, Jhonson; Tobing, Artha L. (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study aims to analyze the village government's strategy, inhibiting and supporting factors in increasing community participation in village development planning based on Law No. 3 of 2024 concerning Villages. Community participation in village development planning is a key factor in achieving effective and sustainable development. However, based on previous research findings, community participation in the Development Planning Deliberation (Musrenbang) still faces various challenges, such as low levels of participation, lack of community understanding, and incompatibility of implementation time with daily community activities. This study uses a descriptive qualitative approach with data collection methods through interviews, documentation. Research informants consisted of the Village Head, Village Consultative Body (BPD), and the community of Tanjung Beringin I Village. Data analysis was carried out with reference to Geoff Mulgan's (2009) government strategy theory, which includes five main indicators: objectives, environment, direction, action, and learning. The results of the study show that the village government has implemented various strategies to increase community participation, such as adjusting the Musrenbang schedule with community activities, taking a direct approach, and using social media for socialization. However, there are still obstacles such as community apathy, difficult geographical conditions, and distrust of the planning process. Supporting factors for community participation include the suitability of the program to the needs of the community and a strong culture of mutual cooperation.